2015
DOI: 10.1097/wno.0000000000000182
|View full text |Cite
|
Sign up to set email alerts
|

Homonymous Ganglion Cell Layer Thinning After Isolated Occipital Lesion

Abstract: A 48-year-old man was examined 24 months after medial and surgical treatment of an isolated well-circumscribed right occipital lobe abscess. An asymptomatic residual left homonymous inferior scotoma was present. Fundus examination revealed temporal pallor of both optic discs, and optical coherence tomography (OCT) revealed mild temporal loss of retinal nerve fiber layer in both eyes. No relative afferent pupillary defect was present. Assessment of the retinal ganglion cell layer demonstrated homonymous thinnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 10 publications
4
16
0
Order By: Relevance
“…Previous reports showed that transsynaptic retrograde neurodegeneration (TRD) after post-thalamic visual area (occipital lobe) stroke was high after the first few years and fairly stable over the years (Cowey et al, 2011;Jindahra et al, 2012;Meier et al, 2015;Schneider et al, 2019). In our previous report (Ye et al, 2022), thalamic infarction patients with a duration of more than 6 months also showed a thinner retinal structure compared to patients with a duration of fewer than 6 months.…”
Section: Discussionmentioning
confidence: 59%
“…Previous reports showed that transsynaptic retrograde neurodegeneration (TRD) after post-thalamic visual area (occipital lobe) stroke was high after the first few years and fairly stable over the years (Cowey et al, 2011;Jindahra et al, 2012;Meier et al, 2015;Schneider et al, 2019). In our previous report (Ye et al, 2022), thalamic infarction patients with a duration of more than 6 months also showed a thinner retinal structure compared to patients with a duration of fewer than 6 months.…”
Section: Discussionmentioning
confidence: 59%
“…OCT studies of acquired occipital lobe lesions in humans have demonstrated circumpapillary retinal nerve fibre layer (cpRNFL) thinning with the use of TD-OCT, 4-6 and SD-OCT. [7][8][9]17 In the SD-OCT studies, inner retinal thinning was observed in both the peripapillary and macular areas, in accordance with the patients' hemianopic visual field defects. [9][10][11][12][13][14][15][16]18,23 GCC thinning has been demonstrated in the hemiretinae corresponding to the affected hemifields. Furthermore, macular measurements showed localised defects of RGCs more clearly than peripapillary measurements.…”
Section: Discussionmentioning
confidence: 99%
“…In these SD-OCT studies, inner retinal thinning was observed in both the peripapillary and macular areas, in accordance with the patients' hemianopic visual field defects. [9][10][11][12][13][14][15][16][17][18] More recently, sweptsource OCT (SS-OCT), which permits even faster scanning, has been used to study inner retinal thinning in homonymous hemianopia. 19 Recent advancements in spectral-domain optical coherence tomography (SD-OCT) has enabled the assessment of the RGC layer and the ganglion cell complex (GCC), which includes the retinal layers from the internal limiting membrane to the inner plexiform layer.…”
Section: Introductionmentioning
confidence: 99%
“…TRD in human visual system has been demonstrated in many studies. 2,3,6,[12][13][14][15][16][17][18][19] Guedes et al reported a case with RNF loss (1) of the patient with postgeniculate lesion had decreased vessel density (1a, 1b), RNFL thickness (1c), and GCC thickness (1d) at peripapillary area. Contralateral eye (2) revealed decreased vessel density (2a, 2b), RNFL thickness (2c), and GCC thickness (2d), especially at nasal sectors.…”
Section: Discussionmentioning
confidence: 99%
“…5 Previous studies in the literature demonstrated that abnormalities of macula GCC occurred earlier than peripapillary RNFL thickness. 15,[22][23][24] Moreover, the interpretation of GCC thinning and related visual field loss is easier. It has a simple mirror-image relationship with the visual field, in contrast to the complex relationship between RNFL bundles and visual field sectors that have been mapped previously.…”
Section: Discussionmentioning
confidence: 99%